Tribological information of contact electrical resistance parameters in the study of oxidation and metal plating processes - Gypka, A.; Lyashuk, O.; Mironov, D.; Khoroshun, R.; Aleksevich, Ya.; Fursa, V.; Hynda, T. (Problems of Tribology, 2026)
The work investigates the regularities of the change in contact electrical resistance in heavily loaded tribosystems under the conditions of transition from oxidation processes to the formation of adaptive metal-clad tribofilms. It is proposed to consider contact electrical resistance as an integral kinetic criterion of the structural and energy state of the frictional contact, which reflects the processes of destruction of oxide and metal-clad layers, activation of friction surfaces, formation of electrically conductive adaptive tribostructures and transition to adhesive contact. The research was carried out according to a scheme that models the contact "camshaft cam - roller pusher" using 42CrMo4 and 16MnCr5 steels, typical for modern heavily loaded components of the gas distribution mechanism of internal combustion engines. It is established that the change in contact electrical resistance has a pronounced kinetic nature and reflects structural and phase transitions in the surface layers of the tribosystem. It is shown that high values ​​correspond to the presence of oxide and tribochemical insulating layers, stable minimum values characterize the formation of adaptive electrically conductive metal-cladding tribofilms, and a sharp decrease in contact electrical resistance indicates the destruction of adaptive tribolayers and the transition to direct metal contact. Critical regimes of force loading and sliding speed are determined, under which the most stable conditions of structural and energy self-organization of surface layers are realized.